AtCube: Performing pathogen-root infection tests on Arabidopsis thaliana in a completely controlled way. (January 2022) - Poveda, Jorge
Abstract: Arabidopsis thaliana represents the main model plant for the experimental analysis of plant genetics and developmental biology of photoautotrophic organisms, due to characteristics such as size, life cycle, fecundity, genetics and its easy experimental manipulation. In turn, A. thaliana is used as a model plant in plant-microorganism interaction studies, being of great importance in the knowledge of the form of infection of numerous plant pathogens. The present work is based on the development of an A. thaliana plant growth system in Phytatray II boxes and culture substrate, trying to establish a system that is free of contamination, completely controlled, self-sufficient, reproducible and standardized, called AtCube. Through the use of different necrotrophic and biotrophic/hemibiotrophic root-pathogens, bacteria, fungi and oomycetes, and the comparison with a conventional system of growth in plots, various results are analyzed on the effects of pathogens on plants and the advantages and differences of the AtCube system. This work makes it possible to highlight that the AtCube system represents a methodology that allows obtaining results similar to other systems but with important advantages regarding its standardization, rigor and reproducibility with respect to studies with A. thaliana and root pathogens. Furthermore, it could represent an equally efficient system in studies with other plant species and the application of foliar pathogens and/or beneficial microorganisms. Highlights: Arabidopsis thaliana is a model plant in plant-microorganism interaction studies. AtCube system is a methodology for A. thaliana -root pathogens studies. AtCube is a system with greater standardization, rigor and reproducibility.